The impact of soil acidity amelioration on groundnut production and sandy soils of Zimbabwe - Hammes, Pieter Snyman, 1941- (University of Pretoria, 2013)
Dissertation (PhD (Plant Production: Agronomy))--University of Pretoria, 2003.